SYSTEMATIC LITERATURE REVIEW PERANAN DIGITAL BAGI USAHA USAHA MIKRO DAN MENENGAH (UMKM) - Sari Lubis, Fitri Amelia; Very, Jhon (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
In the current digital era, many people have used digital as a means for business development. Digital is not only a platform for social interaction, but also an important tool for marketing, branding and business development. Many regions have successfully harnessed the power of social media to drive the growth and success of certain businesses. This article aims to provide a systematic literature review regarding the role of digital for micro and medium enterprises (MSMEs). The method used in this research is Systematic Literature Review (SLR). Systematic literature review (SLR) is a secondary study to map, identify, critically evaluate, consolidate, and collect the results of primary studies on a particular research topic. SLR is defined as the process of identifying, appraising, and interpreting all available research evidence with the goal of providing answers to specific research questions. The application of SLR is to identify, evaluate, and interpret all available and relevant literature related to the research question or domain. From 20,000 data, ± 50 journals were obtained which were almost similar to the research theme which would enter the screening stage using inclusion and exclusion criteria to ensure the quality and relevance of the articles to the themes raised. Digital technology helps MSMEs to grow, become more efficient, and remain competitive in an increasingly digital market.